Studi Pemikiran Nizam Al-Mulk dan Relevansinya dalam Ekonomi Islam Kontemporer - Sholatiah, Sholatiah (Islamic Economics and Business Faculty of UIN Antasari, 2024)
The problems that arise in the implementation of Islamic economic thought from historical times, including the contributions of figures such as Nizam al-Mulk, with modern times today, include Islamic economic concepts proposed by Nizam al-Mulk that are relevant in their historical context, but not always directly applicable in modern times. The research approach in this article uses a literature study with qualitative research methods, which focuses on analyzing the literature related to Nizam al-Mulk and Islamic economics. The research on the study of Nizam al-Mulk's thought in Islamic economics aims to explore, interpret and examine his thoughts in the field of Islamic economics and their relevance to contemporary economic issues. The findings of this study indicate that there are several contributions of thought and relevance to contemporary economic issues from Nizam al-Mulk, namely: economic regulation based on Islamic principles, infrastructure and economic development, fiscal and monetary policy, state financial management, economic empowerment of the people. Thus, Nizam al-Mulk's contributions in the field of Islamic economics not only have historical value, but are also relevant to the economic challenges and issues faced by Muslim societies and the world today. Permasalahan yang muncul dalam implementasi pemikiran ekonomi Islam dari masa sejarah, termasuk kontribusi dari tokoh seperti Nizam al-Mulk, dengan zaman modern saat ini, meliputi konsep-konsep ekonomi Islam yang diusulkan oleh Nizam al-Mulk yang relevan dalam konteks sejarah mereka, tetapi tidak selalu langsung dapat diterapkan di zaman modern. Pendekatan penelitian dalam artikel ini menggunakan studi kepustakaan dengan metode penelitian kualitatif, yang berfokus pada analisis literatur-literatur yang berkaitan dengan Nizam al-Mulk dan ekonomi Islam. Penelitian mengenai studi pemikiran Nizam al-Mulk dalam ekonomi Islam bertujuan untuk menggali, menafsirkan, dan menelaah pemikirannya dalam bidang ekonomi Islam serta relevansinya dengan isu-isu ekonomi kontemporer. Temuan penelitian ini menunjukkan bahwa ada beberapa sumbangan pemikiran dan relevansi dengan isu-isu ekonomi kontemporer dari Nizam al-Mulk, yaitu: pengaturan ekonomi berdasarkan prinsip-prinsip Islam, pembangunan infrastruktur dan ekonomi, kebijakan fiskal dan moneter, pengelolaan keuangan negara, pemberdayaan ekonomi umat. Sehingga, kontribusi Nizam al-Mulk dalam bidang ekonomi Islam tidak hanya memiliki nilai sejarah, tetapi juga relevan dengan tantangan dan isu-isu ekonomi yang dihadapi oleh masyarakat Muslim dan dunia pada masa kini.